Un manuscrit savanty mémoire de quatre siècles de philologie : le Parisinus ar. 2346 - Henri Hugonnard-Roche (Revue des Mondes Musulmans et de la Méditerranée)
The manuscript Parisinus ar. 2346 preserves an exceptional testimony about scientific activity in Christian philosophical circles in Baghdad between the second half of the 9th century and the beginning of the 11th. This manuscript contains copies of Arabic translations of Aristotelian works on logic. It also gives numerous informations about the chain of material transmission of the texts as well as numerous glosses originating from Syriac versions which go back to the 7th century. Several examples are given in the article in order to show how this kind of source is useful for research on the history of both textual studies and ideas.